First results on daytime mesopause OH rotational temperatures using ground-based photometry from equatorial latitudes - Sridharan, R.; Taori, Alok; Gurubaran, S.; Rajaram, R.; Shepherd, M. G. (My University, 1999)
Daytime mesospheric OH and rotational temperatures were estimated from the measurements of the relative intensities of the rotational lines in the same vibrational band, using the unique multiwavelength daytime photometer, from Tirunelveli (8.7°N; 77.8°E; 0.5°N dip latitude), an equatorial station in the Indian zone. On a couple of days when simultaneous measurements were available in the vicinity of the experimental site, the estimated temperatures compared well with those measured by the Wind Imaging Interferometer (WINDII) onboard the Upper Atmosphere Research Satellite (UARS). These results, the first of their kind, revealed: (1) large day-to-day variabilities; (2) oscillatory features with periodicities ranging from 0.5 to 6 h; and (3) large deviations of ±30–50 K, on occasions, from the MSIS-90 model temperatures. Comparisons have also been made with simultaneous measurements of neutral winds around mesopause altitudes using the Partial Reflection radar from the same site to look for any possible association of neutral dynamical parameters with the mesopause temperature variabilities. These results are presented and discussed.
Keywords: Partial reflection radar; Upper Atmosphere Research Satellite (UARS); Wind Imaging Interferometer (WINDII); Equatorial latitudes